COMPARISON OF ANTI-INFLAMMATORY AND ANTI-NOCICEPTIVE ACTIVITIES OF CURCUMA WENYUJIN Y.H. CHEN ET C. LING AND SCUTELLARIA BAICALENSIS GEORGI - Zhou, Jue; Qu, Fan; Zhang, Hang-Jun; Zhuge, Xiao-Hong; Cheng, Liang-Zhong (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The study aimed to compare the anti-inflammatory and anti-nociceptive activities of Curcuma wenyujin Y.H. Chen et C. Ling (Curcuma wenyujin) and Scutellaria baicalensis Georgi (Scutellaria baicalensis). This study used three parts to compare the two herbs. Firstly, animals were randomly divided into a Scutellaria baicalensis group, a Curcuma wenyujin group, an indomethacin group, and a model-control group to perform an ear edema test, a carrageenin-induced paw edema test, a cotton pellet-induced granuloma formation test, and an acetic acid-induced writhing test. Secondly, model rats with pelvic inflammation were established, and the serum levels of TNF-Î± and IL-6 in each group was detected with the Enzyme-Linked Immunosorbent Assay (ELISA). Thirdly, pharmacokinetics analysis of Scutellaria baicalensis and Curcuma wenyujin was conducted on the model rats. The ear edema test, carrageenin-induced paw edema test, cotton pellet-induced granuloma formation test, and acetic acid-induced writhing test all showed that Curcuma wenyujin had stronger anti-inflammatory and anti-nociceptive effects than Scutellaria baicalensis. There is significant difference between the effects of Curcuma wenyujin and Scutellaria baicalensis on the levels of TNF-Î± and IL-6 for the model rats. Curcuma wenyujin decreased the levels of TNF-Î± and IL-6 more than Scutellaria baicalensis. The pharmacokinetics analysis showed that curcumol’s Tmax, Cmax, and the area under the curve (AUC) were all higher than baicalin’s. This study indicated that for pelvic inflammation, Curcuma wenyujin had better anti-inflammatory and anti-nociceptive effects than Scutellaria baicalensis.